Effects of Crescentia cujete (L.) fruit extract on the profile of hematology of ranchu goldfish (Carassius auratus) - Felician Lestari Wongkar; Yos Adi Prakoso; Agustina Dwi Wijayanti (Open Veterinary Journal, 2024)
Background: Disease prevention in cultivating ranchu goldfish (Carassius auratus) can be prevented by giving immunostimulants in the food. One immunostimulant can come from herbs such as calabash fruit (Crescentia cujete L.).